"When You Look at This Chart, That Is Not My Whole Life": Caregiver Perspectives to Inform Improved Primary Care Practice and Outcomes - Monique Quinn; Allison Parsons; Chidiogo Anyigbo; Alexandra M. S. Corley; Lauren Lipps; Jamaica Gilliam; Julietta O. Ladipo; Caitlin Jee Hae Behle; Desiré Bennett; Carley Riley (SAGE Publishing, 2024)
Objective: Worsening rates of infant and maternal mortality in the United States serve as an urgent call for multi-modal intervention. Infant Well Child Visits (WCVs) provide an opportunity for prevention, however not all infants receive the recommended schedule of visits, with infants of low-income and Black families missing a higher portion of WCVs. Due to diverse experiences and needs of under-resourced communities throughout the United States, caregiver voice is essential when designing improvement efforts. Methods: Purposeful sampling and interviewing of 10 caregivers in Cincinnati, OH was performed by community peer researchers. Interview transcripts were evaluated by the research team, with identification of several important themes. Results: Nine out of 10 caregivers self-identified as Black. All young children of the interviewed caregivers had Medicaid as their insurance provider. All interviews highlighted rich perspectives on caregiver hopes for their child, family, and selves. Establishing trust through empathy, shared decision making, and the nurturing of interpersonal patient-practitioner relationships is crucial for fostering a positive healthcare experience. Levels of mistrust was perceptibly high across several interviews, with lack of racial concordance between medical provider and family exacerbating the issue for some caregivers. Caregivers voiced a tendency to rely on family and community members for when to seek out health care for their children, and additionally cited racism and perceptions of being rushed or judged as barriers to seeking further care. Conclusion: This study emphasizes the importance of being community-informed when considering interventions. Prior research on the topic of missed WCV's often focused on material resource availability and limitations. While that was commented on by caregivers in this study as well, equal-if not more-attention was directed toward interpersonal relationship formation, the presence or absence of trust between practitioner and caregiver, and the importance of social-emotional support for caregivers. We highlight several opportunities for systemic improvements as well as future directions for research.